Android-based mixed arithmetic operation learning media for mentally retarded students at SLB-C Dharma Rena Ring Putra II - Arfina Maya Ismawati; Alfina Nurhaliza; Lina Rachmawati; Rahila Andini Salsabila; Syariful Fahmi (Universitas Muhammadiyah Magelang, 2022)
The community service at SLB-C Dharma Rena Ring Putra II aims to improve students' understanding of mathematics, especially in the subject of mixed arithmetic operations using the MUTU (Mudah Berhitung) application. In their daily life, mentally retarded students at SLB-C Dharma Rena Ring Putra II are quite difficult in participating in mathematics learning, because they only rely on textbooks, so students cannot focus and the learning process is less than optimal. The service method is carried out in 3 stages, pretest-assistance-posttest. Comparison of pretest and posttest scores showed an increase in the average ability of students in understanding the material and solving mixed arithmetic operations, from 38 to 79. The results were used as a reference for mentally retarded students to improve their understanding of mixed arithmetic operations and become a reference for learning media for teachers at SLB-C Dharma Rena Ring Putra II.